Minimally invasive versus open pancreatoduodenectomy for pancreatic ductal adenocarcinoma: Individual patient data meta-analysis of randomized trials - Uijterwijk, Bas; Wei, Kongyuan; Kasai, Meidai; Ielpo, Benedetto; Hilst, Jony van; Chinnusamy, Palanivelu; Lemmers, Daniel H. L.; Burdio, Fernando; Senthilnathan, Palanisamy; Besselink, Marc G.; Abu Hilal, Mohammed; Qin, Renyi (European journal of surgical oncology, 2023)
Objective - Assessment of minimally invasive pancreatoduodenectomy (MIPD) in patients with pancreatic ductal adenocarcinoma (PDAC) is scarce and limited to non-randomized studies. This study aimed to compare oncological and surgical outcomes after MIPD compared to open pancreatoduodenectomy (OPD) for patients after resectable PDAC from published randomized controlled trials (RCTs). - Methods - A systematic review was performed to identify RCTs comparing MIPD and OPD including PDAC (Jan 2015-July 2021). Individual data of patients with PDAC were requested. Primary outcomes were R0 rate and lymph node yield. Secondary outcomes were blood-loss, operation time, major complications, hospital stay and 90-day mortality. - Results - Overall, 4 RCTs (all addressed laparoscopic MIPD) with 275 patients with PDAC were included. In total, 128 patients underwent laparoscopic MIPD and 147 patients underwent OPD. The R0 rate (risk difference(RD) −1%, P = 0.740) and lymph node yield (mean difference(MD) +1.55, P = 0.305) were comparable between laparoscopic MIPD and OPD. Laparoscopic MIPD was associated with less perioperative blood-loss (MD -91ml, P = 0.026), shorter length of hospital stay (MD -3.8 days, P = 0.044), while operation time was longer (MD +98.5 min, P = 0.003). Major complications (RD -11%, P = 0.302) and 90-day mortality (RD -2%, P = 0.328) were comparable between laparoscopic MIPD and OPD. - Conclusions - This individual patient data meta-analysis of MIPD versus OPD in patients with resectable PDAC suggests that laparoscopic MIPD is non-inferior regarding radicality, lymph node yield, major complications and 90-day mortality and is associated with less blood loss, shorter hospital stay, and longer operation time. The impact on long-term survival and recurrence should be studied in RCTs including robotic MIPD.